On size invariance texture image retrieval by fuzzy logic classifier and scattering statistical features. Issue 2 (May 2016) - Wang, Juan; Zhang, Jiangshe; Zhao, Mingming
Abstract The texture image retrieval plays an important role in everyday life of people. In this paper, a new and efficient image features extraction approach based on scattering transform is proposed for size invariance texture image retrieval. The proposed approach obtains texture information in different directions and scales. And, analysis of size invariance texture image retrieval using fuzzy logic classifier and scattering statistical features is carried out. The different size samples of texture image are randomly generated from the original texture images. Also, average success rate of each size samples is obtained, respectively. The study shows that statistical features can achieve good performance from the sixth feature.